Adaptive habitat preferences in the Tawny Owl Strix aluco. Issue 3 (3rd July 2017) - Rumbutis, Saulius; Vaitkuvienė, Daiva; Grašytė, Gintarė; Dagys, Mindaugas; Dementavičius, Deivis; Treinys, Rimgaudas
ABSTRACT: Capsule: Tawny Owls Strix aluco occupying nest boxes preferred habitats which were positively associated with the probability of nesting success. Aims: We aimed to determine whether or not: (1) Tawny Owls showed habitat preferences when occupying nest boxes; (2) nesting performance was related to the habitats around occupied nest boxes and (3) habitat availability had changed around available and occupied nest boxes between 1995–2004 and 2005–14. Methods: Tawny Owls were studied using nest boxes erected in a commercial forest. During nest boxes checks (724 cases), data on occupancy and nesting performance (88 cases) were recorded, and habitat within a 0.4 km radius around nest boxes was analysed. Results: Tawny Owls had preferences for clearings within forests, mature forests and grasslands but avoided young forests. We found a positive relationship between nesting success and abundance of clearings within the forest, and a negative relationship between nesting success and abundance of young forests. A change in habitat preferences over the two decades was evident, but habitat availabilities remained similar. Conclusions: Findings indicate adaptive habitat selection in Tawny Owls because preferred habitats were associated with higher fitness and this type of habitat became more frequently selected over time.